Effect of Green Tea Extract on Spermatozoa Quality of Peranakan Ongole Bull On Frozen Storage - Giyanita Rahma Ayu Pramesti; Nur Ducha (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Low-temperature storage can often result in spermatozoa damage. It occurs due to Reactive Oxygen Species, leading to changes in the lipid composition of the membrane. Antioxidant compounds are needed to prevent ROS. Green tea extract (Camelia sinensis) can be used as an antioxidant agent. This study aimed to determine the effect of green tea extract in tris egg yolk on spermatozoa quality of Ongole Peranakan (PO) cattle. This study used a completely randomized design (CRD) with five extract treatments (0%, 1%, 2%, 3%,4%) and four repetitions. The parameters used were motility, viability, and membrane integrity. The data were analyzed with ANOVA and Duncan's test. Based on the results of the ANOVA test, the addition of green tea extract has a significant effect on spermatozoa quality of PO cattle in frozen storage (P0.005). The best results were obtained by the addition of 3% extract that was able to maintain the quality of post-freezing spermatozoa with average motility, viability, and membrane integrity of 47.44±0.166, 55.14±0.449, and 53.72±0.599. The addition of 3% green tea extract into tris egg yolk can maintain motility, viability, and membrane integrity in spermatozoa of PO cattle inside frozen storage, by adding green tea extract to diluent, spermatozoa can be stored for a long time at low temperatures making it easier for people to carry out artificial insemination.